From caregiving burden to income transformation: intergenerational employment effects of long-term care insurance - Li, Zhiying; Zheng, Longhua; Xu, Hong (Frontiers in Public Health, 2025)
BackgroundLong-term care insurance (LTCI) has been introduced in China to address the challenges posed by an aging population. This study examines its impact on the income of older adult households, using data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2020. The analysis further explores heterogeneity and implications for income inequality.MethodsA Difference-in-Differences (DID) approach is employed, with 12 pilot cities as the treatment group and non-pilot cities as the control group. The analysis is based on 33,435 valid observations of individuals aged 60 and above. The main outcome variable is per capita household income, which has been deflated to 2011 constant prices using the Consumer Price Index (CPI). Demographic and regional characteristics are controlled for robustness.ResultsLTCI significantly increases the income of older adult households, particularly in multi-child families and among younger older adult (under 75). Its impact is weaker in low- or no-child households and for those aged 75 and above. Additionally, LTCI contributes to reducing income inequality by enhancing income distribution among low-income older adult households.DiscussionThe findings highlight the role of LTCI in improving economic security and narrowing income disparities among older adult households. To enhance its effectiveness, policy adjustments should account for family structure and age composition. These insights provide empirical support for optimizing LTCI to foster a more inclusive social security system.